Self-Adjusment in Mothers Who Have Children with Special Needs with Slow Learner Disorder (Phenomenological) - 'Aini, Jafnah Kamilah; Affandi, Ghozali Rusyid (Universitas Muhammadiyah Ponorogo, 2025)
Self-Adjustment is a phenomenon often experienced by parents who have children with special needs. Self-Adjustment is an important aspect in dealing with the emotional, social and psychological challenges that arise due to the child's condition. Self-Adjustment is the process of each individual learning to adapt to a new environment. This occurs when each individual faces a new situation and needs to respond. This study uses a qualitative research method with a phenomenological approach with data collection techniques using semi-structured interviews. In this research participants used purposive sampling technique with the criteria of two mothers who have children with special needs with slow learner disorders who attend private elementary school X in the Sidoarjo area - East Java Province. The results showed that mothers who have children with special needs with slow learner disorders experience various challenges. Both participants had children with special needs with slow leaner disorders with different problems. Both participants experienced challenges such as social pressure, stress, excessive emotionality, ability to adapt and ability to learn. Although both participants faced various challenges, participants were able to learn and benefit from the experiences they had. Thus, participants can become more patient, grateful and strong and ready to face a more stable life. This study aims to determine the extent of the phenomenon of Self-Adjusment in mothers who have children with special needs with slow learner disorders. This research is expected to provide new insights to contribute real support for mothers who have children with special needs with mild or severe categories. So that it is useful for improving the psychological well-being of parents, especially for mothers.